Characterization of Surface Runoff, Soil Erosion and Nutrient Loss on Forest-Agriculture Landscape - Hidayat, Yayat; Murtilaksono, Kukuh; Sinukaban, Naik (UNIVERSITY OF LAMPUNG, 2012)
The study was aimed to quantify volume of surface runoff, soil erosion and nutrient loss from the forest-agriculture landscape (forest margins) in Lore Lindu National Park Central Sulawesi. Surface runoff volume and soil erosion were measured daily on erosion plots. It was installed on several land use types i.e. forest land, maize, young cocoa, medium cocoa, old cocoa, vanilla, shrub and bush and bareland, on the soil Typic Dystrudepts with slope ± 40%. The nutrient content in surface runoff and sediments were analyzed from selected surface runoff and sediment samples. Surface runoff and soil erosion from agriculture land were respectively 2.1 to 3.4 and 3.6 to 5.8 times higher than from forest lands. Meanwhile, surface runoff and soil erosion from bareland were respectively 7.0 and 23.7 times greater than forest land respectively. Sediment nutrient contents from forest land were higher than agriculture land. In the contrary, total nutrient lost from agriculture land were higher than forest land ones. Nutrient losses carried by surface runoff were larger than those losses carried by sediments. Dissolved organic carbon (DOC) loss in surface runoff was 6,1 to 8,0 times higher than total organic carbon (TOC) loss in sediments. Likewise, nitrate (NO3-) loss in surface runoff was 1.9 to 12.1 times higher than total nitrogen (TN) in sediments as well as potassium, calcium, magnesium and sodium losses. Potassium is dominant cation loss carried by the surface runoff, while calcium is mainly carried by sediment.Keywords: Dissolve organic carbon; forest-agriculture landscape; nutrient loss; soil erosion; surface runoff[How to Cite: Hidayat Y, K Murtilaksono and N Sinukaban. 2012. Characterization of Surface Runoff, Soil Erosion and Nutrient Loss on Forest-agriculture Landscape. J Trop Soils, 17 (3): 259-266. doi: 10.5400/jts.2012.17.3.259][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.259]